2017
DOI: 10.1097/md.0000000000004635
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus as a uropathogen in an Irish setting

Abstract: Urinary tract infections are one of the most common infectious diseases diagnosed in the community and in the hospital setting. Their treatment is complicated by drug-resistant pathogens and the colonization by microbes of indwelling urinary catheters. This study assessed the occurrence and antimicrobial susceptibility of methicillin-resistant Staphylococcus aureus (MRSA) uropathogens isolated for 5 consecutive years at University Hospital Waterford between 2010 and 2014. We created 4 clinically relevant subdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 14 publications
3
23
1
1
Order By: Relevance
“…Among gram-positive bacteria, 38% of S. aureus were MRSA; 95% of were resistant to penicillin, 60% to cephalexin and 54% to cotrimoxazole. A study conducted in Ireland concluded that 27.8% of S. aureus isolated from urine samples were MRSA [40]. Recent studies have reported the increasing prevalence of multi drug resistant S. aureus especially MRSA in UTIs [40, 41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among gram-positive bacteria, 38% of S. aureus were MRSA; 95% of were resistant to penicillin, 60% to cephalexin and 54% to cotrimoxazole. A study conducted in Ireland concluded that 27.8% of S. aureus isolated from urine samples were MRSA [40]. Recent studies have reported the increasing prevalence of multi drug resistant S. aureus especially MRSA in UTIs [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Ireland concluded that 27.8% of S. aureus isolated from urine samples were MRSA [40]. Recent studies have reported the increasing prevalence of multi drug resistant S. aureus especially MRSA in UTIs [40, 41]. Among E. faecalis, 95% were resistant to amikacin, 69% to penicillin and 68% towards ofloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…UTIs represent more than 30% of all healthcare-associated infections [ 112 ]. Most of the UTIs are caused by the uropathogenic E. coli , although MRSA is becoming an increasingly important uropathogen in the hospital setting [ 38 , 39 , 113 ]. It is disconcerting that 22% of patients in which urine MRSA was detected, developed invasive infections with MRSA in the next 12 months, such as endocarditis, osteomyelitis, and skin and soft tissue infections [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increasing number of bacterial strains are multidrug resistant, which further limits the impact of the available antimicrobial agents [ 33 ]. UTIs are one of the most common healthcare-associated infections and reports of multidrug-resistant bacteria causing UTIs [ 37 ], especially methicillin-resistant Staphylococcus aureus (MRSA) [ 38 , 39 , 40 ], ESBL-producing Escherichia coli [ 41 , 42 , 43 ] and Klebsiella pneumoniae [ 7 , 44 , 45 ], multidrug-resistant Acinetobacter baumannii [ 46 , 47 , 48 ], vancomycin-resistant Enterococci (VRE) [ 49 , 50 , 51 ], and Pseudomonas aeruginosa [ 46 , 52 , 53 ], are increasing. All of these bacteria were included on the list of priority pathogens for research and development of new antibiotics published by the World Health Organization (WHO) in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…These are the common gram positive bacteria usually responsible for skin and soft tissue infections but rarely cause CAUTI and bacteraemia [85]. The incidence of Staphylococcal UTI as well as CAUTI is increasing and the organisms carry wide variety of multidrug-resistant genes on plasmids, which augment spread of resistance among other species [86].…”
Section: Cauti With Staphylococcimentioning
confidence: 99%